2022
DOI: 10.18632/aging.204342
|View full text |Cite
|
Sign up to set email alerts
|

Lamin A to Z in normal aging

Abstract: Almost since the discovery that mutations in the LMNA gene, encoding the nuclear structure components lamin A and C, lead to Hutchinson-Gilford progeria syndrome, people have speculated that lamins may have a role in normal aging. The most common HPGS mutation creates a splice variant of lamin A, progerin, which promotes accelerated aging pathology. While some evidence exists that progerin accumulates with normal aging, an increasing body of work indicates that prelamin A, a precursor of lamin A prior to C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…We and others also showed that Lonafarnib decreases the proliferation of HGPS cells (Figure 1l,m and ref 31 ). In addition, the effect of Lonafarnib on delaying physiological aging is questionable as the role of progerin in physiological aging has yet to be established (Primmer et al., 2022 ). On the contrary, mitophagy activator UMI‐77 exhibits no significant toxicity in HGPS cells or mice (Figure 1l,m and Figure S6G–K ).…”
Section: Discussionmentioning
confidence: 99%
“…We and others also showed that Lonafarnib decreases the proliferation of HGPS cells (Figure 1l,m and ref 31 ). In addition, the effect of Lonafarnib on delaying physiological aging is questionable as the role of progerin in physiological aging has yet to be established (Primmer et al., 2022 ). On the contrary, mitophagy activator UMI‐77 exhibits no significant toxicity in HGPS cells or mice (Figure 1l,m and Figure S6G–K ).…”
Section: Discussionmentioning
confidence: 99%
“…12 Nutritional or pharmacological activation of autophagy or mitophagy (which is mitochondrionspecific autophagy) can delay HGPS in mouse models. 13,14 It appears that both prelamin A and progerin contribute to nonsyndromic aging (outside of HGPS) as well, 15 calling for diagnostic tests to measure their abundance and then to appropriately treat the affected subpopulation of patients.…”
Section: Lmnamentioning
confidence: 99%
“…HGPS patients and mouse models develop typical premature aged features and age‐related disorders such as atherosclerosis, cardiovascular disease, and osteoporosis associated with low bone mass, increased fracture risk, and osteolysis of the ribs (Hamczyk et al., 2018 ; Merideth et al., 2008 ; Osmanagic‐Myers et al., 2019 ). On the cellular level, progerin‐expressing cells display typical aging hallmarks (Lopez‐Otin et al., 2023 ) such as epigenetic changes, reduction in telomere length, increased DNA damage, and genomic instability associated with the development of stable cell cycle arrest named cellular senescence (Cenni et al., 2020 ; Manakanatas et al., 2022 ; Mojiri et al., 2021 ; Primmer et al., 2022 ). Accordingly, we and others could demonstrate that progerin expression in ECs of Prog‐Tg mice results in the accumulation of senescent ECs in tissues with similar findings in human ECs derived from induced pluripotent stem cells of HGPS children (Manakanatas et al., 2022 ; Mojiri et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%